2015
DOI: 10.1007/s00027-015-0461-0
|View full text |Cite
|
Sign up to set email alerts
|

Transformations in DOC along a source to sea continuum; impacts of photo-degradation, biological processes and mixing

Abstract: Peatlands export significant amounts of Dissolved Organic Carbon (DOC) to freshwaters, but the quantity of DOC reaching marine environments is typically less than the input to the fluvial system due to processing within the water column. Key removal processes include photo-chemical degradation, and heterotrophic bacterial respiration. In this study we examined these processes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 55 publications
3
40
1
Order By: Relevance
“…This result corroborates that riverine DOC is regulated by a series of complex and interactively connected processes [17]. Climatic and hydrological factors mainly affect temporal variability rather than spatial distribution of riverine DOC [46,47].…”
Section: Spatial Patterns Of Doc Concentrationssupporting
confidence: 81%
See 1 more Smart Citation
“…This result corroborates that riverine DOC is regulated by a series of complex and interactively connected processes [17]. Climatic and hydrological factors mainly affect temporal variability rather than spatial distribution of riverine DOC [46,47].…”
Section: Spatial Patterns Of Doc Concentrationssupporting
confidence: 81%
“…Previous investigations showed large uncertainties or even contrasting results in explaining riverine DOC using climate variables, soil properties, land cover types, and hydrological conditions [17,46,53]. Our analyses, based on the extensive USGS observational dataset, provide a systematic examination of DOC variability and the associated environmental controls at regional and national scales.…”
Section: Environmental Controls On Doc Concentrationsmentioning
confidence: 96%
“…If temperature solely caused increased reaction rates of photodegradation, there would be no change in carbon release from solutions in near‐blackout conditions at different temperatures; however, this is not the case in this study (Figure ). Other studies of photodegradation rates found little or no change to DOC concentration in near‐blackout conditions (Gennings et al, ; Jones et al, ; Moody et al, ; Obernosterer & Benner, ).…”
Section: Discussionmentioning
confidence: 93%
“…Jones et al () found DOC losses were negatively correlated to SUVA 254 (ratio of absorption at 254 nm to DOC concentration) after artificial irradiation, noting DOC containing a high proportion of high molecular weight coloured or aromatic compounds is more susceptible to UV degradation. The headland streamwater used here can be regarded as “UV‐labile” in comparison with older lake DOC, headwaters having rapid preferential photodegradation of more photosensitive DOC components (Molot & Dillon, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased exports of DOC are problematic for multiple reasons. DOC in fluvial systems can be mineralized to CO 2 , thereby contributing to atmospheric CO 2 concentrations (Cole et al, ; Jones, Evans, Jones, Hill, & Freeman, ). Additionally, DOC affects light attenuation and can therefore affect the functioning of aquatic ecosystems (Karlsson, Byström, Ask, Persson, & Jansson, ), and DOC can bind with trace metals, some toxic (Lawlor & Tipping, ; Rothwell, Evans, Daniels, & Allott, ).…”
Section: Introductionmentioning
confidence: 99%